Imagens dialéticas do audiovisual colaborativo na hitRECord - Rue, Larissa Almeida de la (Universidade do Vale do Rio dos Sinos, 2017)
This thesis addresses the update of the collaborative audiovisual in hitRECord, an open and collaborative production company. The collaborative audiovisual is understood here from the perspective of Bergson (2005) and Deleuze (2004) as a mix of virtual and current. It is an updated in the media and out of it and it has possibilities of numerous new updates. In the context of technoculture, the collaborative audiovisual is thought of as a construct or ethicidade (KILPP, 2010) constructed technically, aesthetically and ethically. Through the Metodologia das Molduras this work turns to the dissection of interfaces (technical images) of hitRECord’s website to find the main molduras, ethicidades and imaginaries. As a last step, we return to the tensest images, the most contradictory meanings in the molduras and ethicidades, elaborating a constellation of dialectical images (BENJAMIN, 2006). To help us better understand the way of production of hitRECord, that is based on remix, we searched in Lev Manovich (2013) and his concept of deep remixability for the main theoretical contribution.
Keywords: HitRECord; Colaborativo; Tecnocultura; Audiovisual colaborativo; Remix; Collaborative; Technoculture; Collaborative audiovisual; ACCNPQ::Ciências Sociais Aplicadas::Comunicação